Nanotheranostics for Cancer Therapy and Detection: State of the Art - Paliwal, Shivani R.; Kenwat, Rameshroo; Maiti, Sabyasachi; Paliwal, Rishi (Current Pharmaceutical Design, 2020)
Nanotheranostics, an approach of combining both diagnosis and therapy, is one of the latest advances in cancer therapy particularly. Nanocarriers designed and derived from inorganic materials such as like gold nanoparticles, silica nanoparticles, magnetic nanoparticles and carbon nanotubes have been explored for tremendous applications in this area. Similarly, nanoparticles composed of some organic material alone or in combination with inorganic nano-cargos have been developed pre-clinically and possess excellent features desired. Photothermal therapy, MRI, simultaneous imaging and delivery, and combination chemotherapy with a diagnosis are a few of the known methods exploring cancer therapy and detection at organ/tissue/molecular/sub-cellular level. This review comprises an overview of the recent reports meant for nano theranostics purposes. Targeted cancer nanotheranostics have been included for understating tumor micro-environment or cell-specific targeting approach employed. A brief account of various strategies is also included for the readers highlighting the mechanism of cancer therapy.
Keywords: imaging